Penerapan Sanksi Pidana Judi Online Dalam Perspektif Hukum Positif dan Hukum Pidana Islam (Analisis Putusan PN Jambi Nomor 68/Pid.B/2020/PN.Jbi) - Gusman, Indra; Rahman, Fuad; Ramlah, Ramlah (CV. Rayyan Dwi Bharata, 2025)
This research aims to analyze and examine in depth the criminal sanctions for online gambling in Article 45 Paragraph (2) of the Republic of Indonesia Law Number 19 of 2016 concerning Information and Electronic Transactions from an Islamic Criminal Law Perspective. To obtain answers to the research focus, this study is directed at library research (Library Research) with primary data sources Republic of Indonesia Law Number 19 of 2016 concerning Information and Electronic Transactions) and Jinayah fiqh study books along with secondary data sources through book studies -books and literature that are relevant to the problem being studied. The data collection method was carried out using document study techniques. After the data has been successfully collected and analyzed. So, based on the analysis of these data, the research results show that the substance of gambling regulations in Republic of Indonesia Law Number 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions, regulates the pattern of crimes committed using computers or the internet as a tool in carrying out crimes, namely those involving gambling, while the regulation of the formulation of the elements of criminal acts of gambling still refers to the Criminal Code, Republic of Indonesia Law Number 7 of 1974 concerning Controlling Gambling, and Government Regulation Number 9 of 1981 concerning Implementation of Controlling Gambling. In the study of fiqh jinayah, gambling is categorized as an act of ta'zir. The ruler has the right to determine the punishment according to his actions. In this case, the government, in eradicating regular gambling or online gambling, provides punishment by applying sanctions, whether contained in the Criminal Code or Law of the Republic of Indonesia Number 19 of 2016. The sanctions that have been determined by the government are takzir punishments. The punishment can vary, in this case prison sentences and fines.